2015
DOI: 10.1002/mgg3.156
|View full text |Cite
|
Sign up to set email alerts
|

EGFR mutations cause a lethal syndrome of epithelial dysfunction with progeroid features

Abstract: The epidermal growth factor receptor (EGFR) is part of a large family of receptors required for communicating extracellular signals through internal tyrosine kinases. Epidermal growth factor (EGF) signaling is required for tissue development, whereas constitutive activation of this signaling pathway is associated with oncogenic transformation. We identified homozygous c.1283G>A (p.Gly428Asp) mutations in the extracellular domain of EGFR in two siblings. The children were born prematurely, had abnormalities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
(17 reference statements)
3
18
0
Order By: Relevance
“…All children in our study were of Roma origin and most of their families are from Eastern Slovakia, strongly supporting a “founder effect” as suggested by Ganetzky et al. …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…All children in our study were of Roma origin and most of their families are from Eastern Slovakia, strongly supporting a “founder effect” as suggested by Ganetzky et al. …”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, the results of our study of 18 children together with three published cases suggest that EGFR deficiency due to the homozygous mutation p.Gly428Asp in EGFR results in a devastating neonatal nephrocutaneous syndrome. The disease is almost always fatal in the neonatal or early infantile period due to skin lesions and severe secondary infections, but as seen in the one surviving boy, extremely demanding skin care with proper management of infections, ion and water imbalances may improve the unfavorable outcome of patients.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Epidermal growth factor receptor (EGFR), a receptor that recognizes EGF, is a very important regulator of cell proliferation and differentiation 2 , 3 . Campbell et al 4 and Ganetzky et al 5 reported on patients with ED who possessed homozygous loss-of-function (LoF) mutations of EGFR . These patients had common biallelic homozygous mutations.…”
mentioning
confidence: 99%
“…From perhaps the earliest report of a homozygous missense mutation in SLC26A3 (Choi et al, 2009) in a patient with Bartter syndrome, a renal saltwasting disease, more than 20 novel and previously uncharacterized genodermatoses, germline and mosaic, have been identified through WES, and many further discoveries are anticipated. Selected recent examples include the discovery of somatic mutations in HRAS and KRAS in nevus sebaceus (Levinsohn et al, 2013) and a new autosomal recessive epithelial inflammatory disease resulting from germline mutations in EGFR (Campbell et al, 2014;Ganetzky et al, 2015). For diagnostic applications, however, there are some limitations to WES, mainly centered on the management and analysis of the large-scale data that are generated.…”
mentioning
confidence: 99%